Investigation of K+K- interactions via femtoscopy in Pb-Pb collisions at √ˢɴɴ =2.76 TeV at the CERN Large Hadron Collider - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; Al-Turany, M.; et al. (American Physical Society, 2023)
Femtoscopic correlations of nonidentical charged kaons (K⁺K⁻) are studied in Pb-Pb collisions at a center-of mass energy per nucleon-nucleon collision √ˢɴɴ = 2.76 TeV by ALICE at the CERN Large Hadron Collider. One-dimensional K⁺K⁻ correlation functions are analyzed in three centrality classes and eight intervals of particle-pair transverse momentum. The Lednický and Luboshitz interaction model used in the K⁺K− análisis includes the final-state Coulomb interactions between kaons and the final-state interaction through aₒ (980) and f₀ (980) resonances. The mass of f₀(980) and coupling were extracted from the fit to K⁺K⁻ correlation functions using the femtoscopic technique. The measured mass and width of the f₀ (980) resonance are consistent with other published measurements. The height of the φ(1020) meson peak present in the K⁺K⁻ correlation function rapidly decreases with increasing source radius, qualitatively in agreement with an inverse volumen dependence. A phenomenological fit to this trend suggests that the φ(1020)meson yield is dominated by particles produced directly from the hadronization of the system. The small fraction subsequently produced by final-state interactions could not be precisely quantified with data presented in this paper and will be assessed in future work.
Keywords: Physics; Hadron; RADIUS; Meson; Nucleon; Particle physics; https://purl.org/pe-repo/ocde/ford#1.03.03